(untitled) (Лучшие интеллектуальные исследования, 2025)
ANNOTATION This article analyzes the duration of growth phases and biometric indicators of chickpea. The research was conducted in the light sierozem soil conditions of Kushrabod district, Samarkand region, focusing on the Yulduz and Uzbekistan-32 varieties. The study examined the duration of germination, budding, flowering, and physiological maturity under different sowing dates (February 25 and March 15). Biometric observations revealed that the Uzbekistan-32 variety grew taller and had a higher first pod height from the ground compared to the Yulduz variety. Early sowing (February 25) showed more favorable growth parameters in both varieties. These results highlight the importance of selecting appropriate sowing times and taking varietal characteristics into account in chickpea cultivation.